The Edutourism of Mangunan Girirejo Yogyakarta: A Plan Strategy in Educational Innovation of Universitas Gadjah Mada - IRWAN, Siti Nurul Rofiqo; ROGOMULYO, Rohlan; SUPRIHANTO, John; HADI, Susilo (Journal of Environmental Management and Tourism, 2019)
The richness of natural resources of Indonesia have not been optimally utilized. Mangunan Girirejo (MaGir) Yogyakarta is the location of Agrotechnology Innovation Centre (PIAT) Universitas Gadjah Mada (UGM). The potential of the local community and physical characteristics of farmland and landscape in MaGir has been planned as a plant collection of fruits and herbs. This research is to create a plan strategy on developing edutourism in the whole concept of agritourism in PIAT MaGir. Methods of data collection used survey methods consisted of observation, documentation, in-depth interview and Focus Group Discussion (FGD). The collected data were analyzed by using the Guttman scale, proceeded by SWOT four quadrant matrix model. The results showed edutourism development strategy of PIAT MaGir UGM that based on the SWOT-4Q analysis was in quadrant IV position that of diversification strategy. The strategy was formed by positive internal weighted values (strengths- weaknesses) and external negative weighted values (opportunities-threats). Various plan alternatives of diversification strategy are needed to anticipate all interest of stake holders in developing edutourism of PIAT MaGir UGM.